LATE-FLOWERING VARIETIES AND WILD SPECIES OF APPLE-TREE IN THE COLLECTION OF MAIKOP EXPERIMENT STATION OF VIR - O. N. Barsukova (Труды по прикладной ботанике, генетике и селекции)
The varieties and wild species of apple-tree with late flowering and resistance to late spring frosts have been identified within the collection of Maikop Experiment Station of VIR. Characteristics of their biological, economical and morphological features have been given. They are recommended as source material for breeding new varieties with high resistance to late spring frosts.